Cognitive behaviour therapy for anxious paediatric dental patients: a systematic review. Issue 5 (8th July 2018) - Gomes, Heloisa Sousa; Viana, Karolline Alves; Batista, Aline Carvalho; Costa, Luciane Rezende; Hosey, Marie Therese; Newton, Tim
Abstract : Background: There is a paucity of evidence about cognitive behaviour therapy in the management of dentally anxious children. Aim: To systematically review evidence of the effectiveness of cognitive behaviour therapy for children with dental anxiety or dental phobia. Design: Clinical trial registries, grey literature, and electronic databases, including The Cochrane Library, EMBASE, PubMed, Scopus, Web of Science, LILACS/BBO, and PsycINFO, were searched (April 2018). The reference lists of relevant studies were hand‐searched. Randomised controlled trials that evaluated the effects of cognitive behaviour therapy on dental anxiety or on acceptance of dental treatment in dental patients up to 18 years were included. Two trained and calibrated reviewers performed the study selection and risk of bias assessment. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Six studies with a total of 269 patients, aged 41 months to 18 years, were included. Cognitive behaviour therapy decreased level of anxiety compared to control groups and improved cooperation/behaviour, although the quality of the evidence was low. Conclusions: Cognitive behaviour therapy produces better anxiety reduction than diverse behavioural management techniques but the evidence was of low quality and further studies in children are needed.